Ease of use, feasibility and inter‐rater reliability of the refined Cue Utilization and Engagement in Dementia (CUED) mealtime video‐coding scheme - Liu, Wen; Batchelor, Melissa; Williams, Kristine (Journal of advanced nursing, 2020)
Aims To refine the Cue Utilization and Engagement in Dementia mealtime video‐coding scheme and examine its ease of use, feasibility, and inter‐rater reliability in assessing the food intake process and dyadic verbal and nonverbal interactions. Design This study was a secondary analysis of 110 videotaped observations of mealtime interactions collected under usual care conditions from a dementia communication trial during 2011–2014. Methods The videos involved 29 staff and 25 residents with dementia (42 unique staff‐resident dyads) in nine nursing homes. Data coding and analysis were performed in 2018–2019. Logs of coding challenges with matched solutions and coding time were collected. Inter‐rater reliability was examined through rating of randomly selected 22 videos across four trained coders. Results It took a mean of 10.81 hr to code a one‐hour video using the refined coding scheme. Coding challenges, including identification of key intake process characteristics and differentiation of similar verbal or nonverbal behaviours, were identified with appropriate solutions. The refined coding scheme had good inter‐rater reliability (Cohen's Kappa range = 0.93 – 0.99, 95% CI = 0.92 – 0.99). Conclusion Findings supported preliminary evidence on feasibility, usability and inter‐rater reliability of the refined coding scheme. Future psychometric testing is needed in diverse populations with dementia across different care settings. Impact Existing tools assessing the food intake process and dyadic interactions are few and have limited feasibility and/or reliability and fail to capture the complexity and dynamics of mealtime care. The refined coding scheme showed preliminary feasibility, usability, and inter‐rater reliability. In consideration of the balance between time intensity and the richness of data obtained, the tool may be appropriate and useful in addressing certain research inquires (e.g., characterizing and clustering dyadic behaviours, temporal relationship between behaviours and intake) pertaining older adults with or without dementia and their formal or informal caregivers. 摘要 目的 完善痴呆患者线索利用与参与及进餐时间视频编码方案,并在患者评估食物摄取过程、二元言语互动和非言语互动时,检查该方案的易用性、可行性和评价者间的可靠性。 设计 这项研究是对2011年至2014年间通过痴呆症交流试验收集的110个日常护理条件下的进餐互动的录像观察的二次分析。 方法 这些视频与9家养老院的29名员工和25名患有痴呆症的居民(42名独特的员工兼居民)相关。数据编码和分析程序均于2018‐2019年进行。收集附有匹配的解决方案和编码时间的编码挑战日志。具体而言,应对四名训练有素的编码员随机选择的22个视频进行评分,以此检验评分员的可靠性。 结果 如果使用改进后的编码方案,则每编码一个时长一小时的视频,平均需要10.81小时。编码挑战已经被确定为适当的解决方案,包括识别关键的摄入过程特征和区分相似的言语或非言语行为等。改进的编码方案具有良好的等级间可靠性(Cohens Kappa范围=0.93–0.99,95%置信区间=0.92–0.99)。 结论 调查结果可用作初步证据,对改进编码方案的可行性、可用性和评分者间可靠性进行证明。未来的心理测量试验需要在不同护理环境下进行,并且试验对象应为不同痴呆人群。 影响 现有的评估食物摄入过程和二元相互作用的工具较少,其可行性和/或可靠性有限,无法用于获取进餐护理的复杂性和动态性等相关信息。改进后的编码方案可显示初步的可行性、可用性和等级间可靠性。考虑到时间强度和获得的数据丰富性之间的平衡,可以使用该工具,以便解决与患有或未患有痴呆症的老年人及其正式或非正式护理者有关的部分研究问题(例如,表征和聚类并元行为,以及行为与摄入量之间的时间关系等)